Study of the effect of plasticizers on the properties of enteric coated diclofenac sodium tablets using Eudragit L - Mansour, Taimmaa; Tamim Hammad (Latakia University Journal -Medical Sciences Series, 2024)
This research aims to study the effect of the type and quantity of plasticizers on the release of diclofenac sodium from its enteric- coated tablets. Several formulations of enteric coated diclofenac sodium tablets were prepared using Eudragit L as a polymer at a concentration of 2%. The different properties of granules and tablets (before and after coating) were evaluated. The effect of different plasticizers (propylene glycol and Span 80 at concentrations of 15% and 30% by weight of the solid polymer) on the release of diclofenac sodium from enteric-coated tablets was studied. The plasticizers used had no significant effect on the release of diclofenac sodium in 0.1N HCl medium. Whereas the percentage of diclofenac sodium released into the phosphate buffer (pH = 6.8) increases from formulas containing the propylene glycol (PG) plasticizer compared to formulas containing the Span 80 plasticizer. The released percentage of diclofenac sodium also increased by increasing the concentration of PG plasticizer, while the released percentage of diclofenac decreased by increasing the concentration of Span 80 plasticizer.